Los retos de lo local en lo global: aportes analíticos y normativos - Sánchez, Jeannette (2006)
This article presents a critical review on the papers that aim the central topic of Íconos 24: “global and local issues in the rural environment”. The articles analyze a very important theme for Ecuador, just when it is on discussion the Free Trade Agreement with the United States. The proposed debate, however, goes beyond the conjuncture and studies the deep structural conflicts among the heterogeneous rural communities to cope with the openness and the absorption of the globalization process, even if there would be some favorable room for local development under the new circumstances. On this task, the authors convey theoretical discussions, comparative analysis, re-readings of history and structural analysis. This review stresses the theoretical, methodological and normative contributions of the dossier’s authors.